Specific CD4 + T-Cell Reactivity and Cytokine Release in Different Clinical Presentations of Leptospirosis - Volz, Magdalena Sarah; Moos, Verena; Allers, Kristina; Luge, Enno; Mayer-Scholl, Anne; Nöckler, Karsten; Loddenkemper, Christoph; Jansen, Andreas; Schneider, Thomas (Clinical and vaccine immunology, 2015)
Clinical manifestations of leptospirosis are highly variable: from asymptomatic to severe and potentially fatal. The outcome of the disease is usually determined in the immunological phase, beginning in the second week of symptoms. The underlying mechanisms, predictive factors, and individual immune responses that contribute to clinical variations are not well understood. The aim of this study was to determine the specifics of CD4 + T-cell reactivity and cytokine release after stimulation with leptospiral antigens in patients with leptospirosis of different disease severities (patients with mild and severe symptoms) and in control subjects (with and without proven exposure to Leptospira ). Whole-blood specimens were stimulated with Leptospira antigens in vitro . Subsequently, intracellular staining of cytokines was performed, and flow cytometry was used to assess the expression of CD40 ligand (CD40L) and the production of gamma interferon (IFN-γ), interleukin-10 (IL-10), IL-2, and tumor necrosis factor alpha (TNF-α) by CD4 + T cells. The production of inflammatory cytokines such as TNF-α by CD4 + T cells after stimulation with leptospiral antigens was highest in patients with severe disease. In contrast, the ratio of IL-10 production to TNF-α production was higher in exposed subjects than in patients with mild and severe disease. Levels of proinflammatory cytokines such as TNF-α may be useful markers of the severity of the immunological phase of leptospirosis. IL-10 production by T cells after antigen-specific stimulation may indicate a more successful downregulation of the inflammatory response and may contribute to an asymptomatic course of the disease.